Muslim’s trust property issues in Malaysia: A preliminary study / Luqman Abdullah ... [et al.] - Abdullah, Luqman; Rosele, Muhammad Ikhlas; Mohd Razif, Nor Fahimah; Ali, Abdul Karim; Abdul Rahman, Noor Naemah (Universiti Teknologi Mara Selangor, 2019)
Wealth or property is an essential part of Muslim life whether it is related to religious affairs or life preservation. Therefore, the trust property management aspect should be emphasized in preserving the benefits of society, especially Muslims. For this reason, this study will review the management of Muslim property trusts in Malaysia and issues related to it. This study was conducted based on a qualitative approach in identifying issues that arose in the management of property trusts. The findings show that there are some issues especially in the management of zakat, waqf, bequeathal and inheritance have become polemic and debate in Malaysia. These issues need to be assessed and resolved from the perspective of Islamic law.